An articulated skeleton of a small individual of Diademodon (Therapsida; Cynodontia) - Gow, C. E.; Grine, F. E. (Bernard Price Institute for Palaeontological Research, 1979)
This paper records a nearly complete, articulated skeleton of Diademodan in undoubted association with a skull of that animal. Previously, only portions of postcranial skeleton have been found in association with cranial remains of this genus. The skeleton is that of a relatively small (ontogenetically young) individual. Skeletal proportions are tabulated, rib and vertebral differentiation is described and discussed. Diademodon is shown to have had a long tail.
Main article
Keywords: Diademodon; skulls; postcrania